1980
DOI: 10.1073/pnas.77.6.3649
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of multiplication-stimulating activity, an insulin-like growth factor, in fetal rat serum.

Abstract: Multiplication-stimulating activity (MSA), purified from medium conditioned by the BRL-3A rat liver cell line, previously has been shown to be closely related to the human somatomedins or insulin-like growth factors. A radioimmunoassay was utilized to measure MSA levels in sera from fetal, maternal, and young rats. A serum somatomedin-binding protein was found to interfere in the radioimmunoassay by competing with antibody for binding 125-Ilabeled MSA. Therefore, prior to radioimmunoassay, sera were filtered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
3
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(151 citation statements)
references
References 21 publications
(31 reference statements)
8
139
3
1
Order By: Relevance
“…The matrix concentrations of IGF-ll in the vehicle-treated animals did not significantly change with time either. There was a remarkable 60% decline in circulating IGF-II during the course of the experiment (P = 0.0001, ANOVA), indicating that the decline in serum IGF-II that can be observed in rats within a few days after birth (21,22), continues into early adulthood (Fig. 4 B).…”
Section: Resultsmentioning
confidence: 87%
“…The matrix concentrations of IGF-ll in the vehicle-treated animals did not significantly change with time either. There was a remarkable 60% decline in circulating IGF-II during the course of the experiment (P = 0.0001, ANOVA), indicating that the decline in serum IGF-II that can be observed in rats within a few days after birth (21,22), continues into early adulthood (Fig. 4 B).…”
Section: Resultsmentioning
confidence: 87%
“…Expression of the insulin-like growth factor-II (IGF-11) gene is greater during foetal development than at any other period in the life of mammals [29,30,40]. Moreover, the disruption of this gene greatly diminishes prenatal growth in mice [6].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I blood levels are low in fetal life compared to postnatal values (Gluckman et al, 1983;Spencer GSG et al, 1983); in contrast, IGF-11 levels were found to be high in the fetus of some species (Moses et al, 1980). However, a direct study of the effect of IGF-11 on fetal growth has failed to show any positive effect on the growth of pig fetuses (Spencer, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Thigh muscle was removed, weighed and frozen in liquid nitrogen and stored at -20 °C for later measurement of DNA, RNA and protein content (Wannemacher et al, 1965;Munro and Fleck, 1966;Abraham et al, 1972 Ashton and Francis, 1978;Weidman and Bala, 1980) and the ability of tissues such as chick liver cells (Haselbacher et al, 1980) and chick cartilage (Burch et al, 1986), to synthesize IGF-I (d'Ercole et al, 1976), it is widely believed that IGF-11 may be the somatomedin involved in growth promotion in the fetus (Moses et al, 1980). IGF-I blood levels are low in fetal life compared to postnatal values (Gluckman et al, 1983;Spencer GSG et al, 1983); in contrast, IGF-11 levels were found to be high in the fetus of some species (Moses et al, 1980).…”
Section: Methodsmentioning
confidence: 99%